2021
DOI: 10.1021/acs.inorgchem.1c01076
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Superheavy Element 115, Mc, and Its Lighter Homologue, Bi, with Respect to Gold and Hydroxylated Quartz Surfaces from Periodic Relativistic DFT Calculations: A Comparison with Element 113, Nh

Abstract: Adsorption energies (E ads) of the superheavy element (SHE) Mc, its lighter homologue (Bi), as well as of another superheavy element Nh and some lighter homologues of SHEs on gold and hydroxylated quartz surfaces are predicted via periodic relativistic density functional theory calculations. The aim of this study is to support “one-atom-at-a-time” gas-phase chromatography experiments that are examining the reactivity and volatility of Mc. The obtained E ads values of the Bi and Mc atoms on the Au(111) surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…23,24 Periodic calculations via the VASP computational package based on the projector-aug-mented plane-wave (PAW) method and pseudopotentials 25 also appeared, with results being overall in good agreement with ours. [20][21][22] The results of all those calculations have shown that Cn should be more volatile than Hg over gold, which is a relativistic effect, however, still forming the Cn-Au chemical bond. 21,22 For Fl, the calculations have shown that it should interact with gold more strongly than Cn, but much more weakly than Pb, which is also a relativistic effect 21,22,25 (see the values in the summary table below).…”
Section: A Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Periodic calculations via the VASP computational package based on the projector-aug-mented plane-wave (PAW) method and pseudopotentials 25 also appeared, with results being overall in good agreement with ours. [20][21][22] The results of all those calculations have shown that Cn should be more volatile than Hg over gold, which is a relativistic effect, however, still forming the Cn-Au chemical bond. 21,22 For Fl, the calculations have shown that it should interact with gold more strongly than Cn, but much more weakly than Pb, which is also a relativistic effect 21,22,25 (see the values in the summary table below).…”
Section: A Introductionmentioning
confidence: 99%
“…[20][21][22] The results of all those calculations have shown that Cn should be more volatile than Hg over gold, which is a relativistic effect, however, still forming the Cn-Au chemical bond. 21,22 For Fl, the calculations have shown that it should interact with gold more strongly than Cn, but much more weakly than Pb, which is also a relativistic effect 21,22,25 (see the values in the summary table below).…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the reactivity of both Mc and Nh has to be taken into account. Nihonium and moscovium are predicted to be less reactive than their nearest homologues Tl and Bi, respectively ( Pershina et al, 2009 ; Fox-Beyer and van Wüllen, 2012 ; Rusakov et al, 2013 ; Pershina, 2016 ; Pershina and Iliaš, 2019 ; Trombach et al, 2019 ; Pershina et al, 2021 ). The calculated first ionization potential ( IP ) of Nh (7.306 eV) ( Eliav et al, 1996 ) is larger than that of Tl (6.11 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The unpaired p 1/ 2 -electron may cause increased chemical reactivity, while the spherical 7p 1/2 orbital is relativistically stabilized. Accordingly, Nh is predicted to be more reactive upon adsorption on gold and quartz surfaces than its neighbors Cn and Fl, but less reactive than Tl, its nearest homologue in group 13 ( Pershina et al, 2009 ; Fox-Beyer and van Wüllen, 2012 ; Rusakov et al, 2013 ; Pershina, 2016 ; Pershina et al, 2021 ). The large spin-orbit splitting in the 7p shell is reflected in its chemical behaviour - Nh appears to be more inert than lighter homologues in the group 13, but can form stable compounds, such as hydrides or hydroxide NhOH.…”
Section: Introductionmentioning
confidence: 99%